Evaluation of Serum Proinflammatory Cytokine IL-17A and Tight Junction Protein Claudin-1 in Psoriasis. (7th March 2022) - Xu, Lina; Pan, Yunlei; Tang, Shunli; Bai, Juan; Wu, Yinhua; Qiao, Jianjun; Fang, Hong
Abstract : Objective . This study aimed to estimate serum IL-17A and Claudin-1 levels, investigate their correlation, and evaluate their diagnostic significance as potential blood-based biomarkers in psoriasis. Methods . Serum IL-17A and Claudin-1 concentrations were determined using enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed to determine differences in serum levels of IL-17A and Claudin-1, their bivariable correlation with psoriasis severity, as Psoriasis Area Severity Index (PASI), and their predictive abilities using receiver operating characteristic (ROC) curves. Results . Significantly higher IL-17A and lower Claudin-1 levels were found in psoriasis (p < 0.05). PASI did not correlate significantly with either IL-17A or Claudin-1 in psoriasis and their subtypes. The only significant correlation between serum IL-17A and Claudin-1 was shown in late-onset psoriasis ( r = 0 . 630, p = 0 . 028 ). ROC curve analysis indicated the serum IL-17A, serum Claudin-1, and combination of IL-17A and serum Claudin-1 for predicting psoriasis with the areas under the curve (AUC) of 0.951 (p < 0.0001), 0.709 (p = 0.0119), and 0.949 (p < 0.0001), respectively. Moreover, the potential role in distinguishing between early-onset and late-onset psoriasis: we obtained serum IL-17A, serum Claudin-1, and their combination AUC of 0.590 (p = 0.3126), 0.741 (p = 0.0045), and 0.741 (p = 0.0067), respectively. However, none of the serum IL-17A, serum Claudin-1, and their combination was well-performed discriminating mild psoriasis from moderate-to-severe psoriasis with AUC of 0.553 (p = 0.5596), 0.518 (p = 0.8539), and 0.559 (p = 0.5225), respectively. Conclusion . These preliminary results suggest that the serum Claudin-1 as a potential biomarker and the relationship and possible regulatory interactions between IL-17A and Claudin-1 in psoriasis are distinguishable by age of onset.